Section Mimadenia: Its phylogenetic relationships within the genus Mimosa (Leguminosae, Mimosoideae) using plastid trnLF sequence data - Bessega, Cecilia Fabiana (2011)
Mimosa L. includes more than 530 species and is subdivided into five sections, including Mimadenia Barneby, Batocaulon DC., Habbasia DC., Calothamnos Barneby and Mimosa. It has previously been proposed that Mimosa is derived from piptadenioid ancestors and that section Mimadenia is a morphological group intermediate between the piptadenoid ancestor and the remaining species from Mimosa. The main goals of the present study were to assess the monophyly of the genus Mimosa as it is currently described, including representatives of all five sections, test the previous evolutionary hypothesis that section Mimadenia is primitive within Mimosa and discuss the infrageneric classification from a phylogenetic view. We report a phylogenetic analysis of chloroplast nucleotide sequences of the trnL intron and the trnLtrnF intergenic spacer from 36 species of Mimosa, and six related genera. Our analysis indicated that genus Mimosa is monophyletic, and the species of section Mimadenia constitute a clade sister to the rest of the genus. Although section Mimadenia, as described by Barneby (1991), seems to be monophyletic, the remaining sections Barneby (1991) proposed are not resolved as monophyletic. An effort needs to be made towards a new infrageneric classification of Mimosa that considers the phylogenetic evidence.